Assembly Line Simulation Model (LACCEI, 2024)
The objective of this paper is to show a simulation model of an assembly line. To this end, the use of the basic ideas of the CDIO initiative and the universally accepted methodology to develop simulation models using the discrete event method are proposed as a development methodology. By applying the methodology, a model of a hypothetical refrigerator assembly line is developed.